2007
DOI: 10.3928/00989134-20070701-06
|View full text |Cite
|
Sign up to set email alerts
|

Older Adult Care in the Emergency Department: Identifying Strategies that Foster Best Practice

Abstract: <h4></h4> <p>The goals of this study were to obtain a profile of older adults who are treated in the emergency department, examine their length of stay and contributing factors, and determine nurses&rsquo; knowledge and perception of care provided to older adults. The records of 206 older adults were reviewed. Emergency department nurses completed the Geriatric Institutional Assessment Profile, which measures knowledge of older adult care. The majority of older patients were community-dwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The ED has been identified as a site that can provide a unique opportunity for conducting an initial screen and collaboration with community agencies (such as aged care facilities) for older adults (Mion et al 2001, Caplan et al 2004. Previous research conducted at this and other (US and Italian) sites identified that older adults in general wait approximately 5-6 hours in the ED before being admitted or discharged (Robinson & Mercer 2007, Crilly et al 2008, Salvi et al 2008. Older adults from ACFs have longer waits (average six hours) in the ED before being admitted or discharged (Crilly et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The ED has been identified as a site that can provide a unique opportunity for conducting an initial screen and collaboration with community agencies (such as aged care facilities) for older adults (Mion et al 2001, Caplan et al 2004. Previous research conducted at this and other (US and Italian) sites identified that older adults in general wait approximately 5-6 hours in the ED before being admitted or discharged (Robinson & Mercer 2007, Crilly et al 2008, Salvi et al 2008. Older adults from ACFs have longer waits (average six hours) in the ED before being admitted or discharged (Crilly et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One study evaluated care in the ED and concluded that nurses scored lower on PrU prevention than on other types of care provided. 23 This suggests that policy focus on nursing home improvements of PrU outcomes needs to expand to hospital treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated an overall Cronbach's Alpha coefficient ranging between 0.60 and 0.65 (42)(43)(44)(45). The GNKA subscale has been used in several published studies (16,(46)(47)(48).…”
Section: Instrumentmentioning
confidence: 99%
“…Several studies indicate that these events are associated with increased morbidity and unfavorable outcomes (12,13). The lack of RN knowledge about these syndromes may act as barriers to using evidence-based geriatric nursing protocols for best practice in clinical practice which could contribute to the older adult's risk for adverse events (14)(15)(16)(17)(18). This can significantly influence RNs practice related to geriatric syndromes, such as the use of restraints (19)(20)(21), the management of pressure ulcers (22,23), urinary incontinence -UI (24)(25)(26)(27)(28), and sleep disturbances (29).…”
Section: Introductionmentioning
confidence: 99%